PENGARUH PENAMBAHAN PATI TALAS BELITUNG (Xanthosoma sagittifolium) TERHADAP SIFAT FISIK YOGURT SUSU KAMBING - Salvian Setyo Prayitno; Anis Ulfah Prastujati; Riski Wahyu Safitri (JURNAL SAINS PETERNAKAN NUSANTARA, 2022)
The purpose of this research was to study determine the effect of adding belitung taro starch on the physical properties of goat's milk yogurt. The addition of belitung taro starch is expected to improve the physical properties of yogurt. The research method used in this study was Completely Randomized Design (CRD). This research was conducted with 4 treatments and 5 repetitions, namely P0 (without Belitung taro starch treatment), P1 (0.5% addition of Belitung taro starch). P2 (addition of 1% Belitung taro starch), P3 (addition of 1.5% Belitung taro starch). The tests carried out in this study included viscosity, syneresis, water holding capacity (WHC), and pH values. The data obtained in this study were analyzed using the Duncan Multiple Range Test (DMRT). The results showed that the addition of belitung taro starch had a very significant (P<0.01) effect on syneresis, viscosity, WHC, and pH values. The addition of belitung taro starch was proven to be able to increase the viscosity, WHC, and pH value, while the syneresis value decreased. The best results for measuring viscosity, WHC, sineresin, and pH were obtained by adding 1.5% (P3) of belitung taro starch. Keywords: belitung taro starch, physical properties, goat's milk, yogurt